What happens in Scotland - McQuiston, Jennifer; Copyright Paperback Collection (Library of Congress) (New York : Avon, 2013)
In 1842, when she wakes up next to a naked Scotsman with a ring on her finger and no recollection of what happened, Lady Georgette Thorold makes a run for it with Highland warrior James MacKenzie fast on her trail.
Includes excerpt from Brighton is for lovers [12 p.].
Keywords: Man-woman relationships -- Fiction; Scotland -- Fiction -- History -- 19th century; Love stories; Historical fiction